Determining the position of indonesian literacy, science and mathematics among PISA participating countries using Multidimensional Scaling Analysis - Niza Niza; Slamet Suyanto; Wan Zuwusni Wan Mustofa; Nurdin Nurdin (Measurement In Educational Research, 2023)
The Program for International Students Assessment (PISA) is a triennial survey of 15-year-old students worldwide. The assessment focuses on core school subjects, namely science, reading, and mathematics. The 2015 PISA survey covers 70 countries, including Indonesia. Indonesia has been participating in the PISA survey since 2000. This article aims to map Indonesia's position towards the PISA participating countries in 2015, which amounted to 72 countries. The analysis used is Multi-Dimensional Scaling (MDS) analysis. The mapping of this position is based on the average value of science, reading, and mathematics. From the analysis results, it is found that Indonesia's position is grouped against the 70 participating countries. From this grouping, it can be seen what Indonesia has taken follow-up actions to improve the quality of education in Indonesia, especially in science, reading, and mathematics subjects.